A novel non-invasive method for evaluating electroencephalograms on laying hens. (17th January 2018) - Eberle, Krista N; Martin, Michael P; Shah, Sanjay; Malheiros, Ramon D; Livingston, Kimberly A; Anderson, Kenneth E
Abstract: The use of electroencephalograms (EEG) to study the avian brain relative to behavior was conducted as early as the 1960's. EEG readings, combined with visual cues, provide the ability to elucidate and correlate behaviors to neurological and physiological changes in a chicken. The use of EEG recordings in animal models require access to the brain to implant electrodes. Having the ability to observe EEG activity on sensible birds without surgical implantation could broaden the research in this area and give further insight related to the hen's state of awareness. The development, construction, and implementation of a minimally invasive EEG electrode placement method is described. After implementation, test animals were exposed to extreme environmental stressors as part of a concurrent depopulation methods study and EEG placement withstood the condition changes and corresponding animal physical activity. Sixteen white commercial laying hens had three monopolar 32-gauge needle electrodes inserted subcutaneously and secured to their head and body. Electrodes were attached to a pre-amplifier which transferred EEG signals to a laptop based recording system. Once the electrodes were in place, the hens were placed in individual treatment/observation chamber then various environmental stressors were applied. Verification that the observed brainwave activity was neural and not muscular was done using a photic stimulation validation test. Behavior observations were recorded to correlate sensible and insensible brainwave activity. The validation test and behavior observations demonstrated the method was successful in measuring EEG in sensible laying hens. The use of a non-surgical method for recording EEG will broaden research capabilities and enhance the understanding of a hen's response its environment, eliminate the need for invasive surgical procedures, and minimizes the confounding components of anesthesia, brain surgery, and recovery. With further refinements, the method could open new avenues in avian behavioral and physiological research.